CONSTRUCTION METHOD FOR LARGE SECTIONAL UNDERGROUND STRUCTURE - NAKADA SHINICHI; FUKAWA TETSUYA; NAGAMITSU KENICHIRO; TAKAHASHI TOSHIYUKI; HATTORI YOSHIFUMI; TOYODA TSUTOMU; HIDAKA NAOTOSHI; IMAISHI TAKASHI (2018)
PROBLEM TO BE SOLVED: To provide a construction method for a large sectional underground structure capable of being safely implemented even in a place with a severe construction condition such as high water pressure or soft ground, and easily constructing a high quality large sectional underground structure while minimizing an effect on a surrounding environment.SOLUTION: A construction method for a large sectional underground structure comprises: a preceding tunnel construction process to juxtapose a plurality of preceding tunnels 2 and 2; a preceding tunnel bar-arrangement process to arrange preceding reinforcement 51 in each preceding tunnel 2; a preceding tunnel filling process to fill each preceding tunnel 2 with preceding infilling concrete 41; a succeeding tunnel construction process to construct a succeeding tunnel 3 between the preceding tunnels 2 and 2 arranged next to each other; and a succeeding tunnel bar-arrangement process to arrange succeeding reinforcement 52 in the succeeding tunnel 3. In the succeeding tunnel construction process, sections of the preceding tunnels 2 and 2 are partially excavated and the succeeding tunnel 3 is constructed in a manner that brings an outer face thereof into contact with the preceding infilling concrete 41.SELECTED DRAWING: Figure 2 【課題】高水圧、軟弱地盤などの施工条件が厳しい場所でも安全に施工することができ、かつ、周辺環境への影響を最小限に抑え、なおかつ、容易に高品質な大断面地中構造物を構築することができる大断面地中構造物の構築方法を提案する。【解決手段】複数本の先行トンネル２，２を並設する先行トンネル施工工程と、各先行トンネル２内に先行鉄筋５１を配筋する先行トンネル配筋工程と、各先行トンネル２内に先行中詰コンクリート４１を充填する先行トンネル充填工程と、隣り合う先行トンネル２，２同士の間に後行トンネル３を構築する後行トンネル施工工程と、後行トンネル３内に後行鉄筋５２を配筋する後行トンネル配筋工程とを備え、後行トンネル施工工程では隣接する先行トンネル２，２の断面の一部を切削するとともに後行トンネル３の外面が先行中詰コンクリート４１に当接するように後行トンネル３を構築する。【選択図】図２